Pengaruh Jenis Mangsa dan Suhu pada Perkembangan Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae) dan Peranannya dalam Pengendalian Diaphorina citri Kuwayama (Hemiptera: Psyllidae) - Tris Haris Ramadhan; Y. Andi Trisyono; Eddy Mahrub; Arman Wijonarko; Siti Subandiyah; George Andrew Charles Beattie (Jurnal Perlindungan Tanaman Indonesia, 2008)
Diaphorina citri Kuwayama (Hemiptera: Psyllidae) is the vector of citrus greening (Huanglongbing) bacterium and the most serious impediment to citrus culture. Classical biological control of this psyllid vector should contribute to suppress their population. This research was conducted to determine the performance of Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae) when they were fed with D. citri. The larval performance index of M. sexmaculatus on D. citri compared with Aphis craccivora Koch (Hemiptera: Aphididae) diet was 1.3.M. sexmaculatus fed with D. citri had lower fitness than those fed with A. craccivora as shown by longer larval stadium, lower adult dry weight, less number of egg produced and lower percentage of egg hatched. M. sexmaculatus grew best at the temperature of 27oC. Employing the exclusion procedure under field condition,M. sexmaculatus could reduce the population of D. citri up to 90%. These findings showed that theM. sexmaculatus could be a potential predator in reducing D. citri, particularly when the more preferred prey A. craccivora was not present.